Emotionally Intelligent Teaching Method: Integrating Social-Emotional Learning (SEL) into EFL Pedagogy in Islamic Senior High Schools of Lombok - Hendra Suryadi; Evi Safitri Yulandari; M. Reka Jaya (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study proposes and empirically examines an Emotionally Intelligent Teaching Method (EITM) that integrates Social-Emotional Learning (SEL) principles into EFL pedagogy in Islamic Senior High Schools across Lombok, Indonesia. Drawing on Mayer and Salovey's Emotional Intelligence Theory and CASEL's five SEL competencies, this quasi-experimental mixed-method research involved 120 students and 10 EFL teachers across three schools. The treatment group received 10 weeks of SEL-infused instruction embedded in communicative tasks, reflective journals, and peer interaction, while the control group followed the standard communicative approach. Quantitative data were collected using pre- and post-tests of language performance and emotional intelligence, while qualitative data were drawn from classroom observations, teacher interviews, and student reflective logs. Results revealed significant improvement in both language achievement (Cohen's d = 0.84, p < .01) and emotional intelligence (?² = .27) in the experimental group, compared with minimal changes in the control group. Qualitative findings confirmed that integrating SEL strategies fostered student motivation, empathy, and confidence in language interaction, aligning with the Islamic values of akhlaq (character) and ukhuwah (social harmony). These outcomes underscore that embedding SEL into EFL teaching not only enhances linguistic competence but also cultivates affective and interpersonal dimensions of learning. The study contributes theoretically to ELT by expanding task-based and affective pedagogy models, and practically by providing a replicable framework for emotionally intelligent teaching in religious schooling contexts.